The influence of Facebook and Twitter on football fanaticism : a study of Arab male students in International Islamic University Malaysia - Ashour, Abdelrahman T A
This study explores the influence of Facebook and Twitter on football fanaticism among Arab male students of International Islamic University Malaysia (IIUM). This study is based on Media Dependency Theory (MDT), which assumes that individuals depend on the media for the information they need. In this study, Arab male students of IIUM who are interested in watching football offer their views on the effects of dependence on Facebook and Twitter as a source of information on the phenomenon of football fanaticism, based on the fact that they are football fans who use these sites to obtain information and watch football matches. This study adopted a qualitative research methodology. In-depth interviews were conducted with nine Arab male students of IIUM. The study sample was chosen based on specific criteria: (1) they must be Arab students at IIUM, (2) they must be football fans, and (3) they must be active users of Facebook and Twitter and comment, post, follow, and disseminate football news. The study attempted to answer three research questions: (1) Why do football fans among IIUM Arab students use Facebook and Twitter to watch football matches? (2) How does the use of Facebook and Twitter lead to football fanaticism? (3) What individual factors lead to football fanaticism? The results of this study show that the football fans among Arab male students of IIUM use Facebook and Twitter because these sites are considered as sources of football news and as platforms for watching football matches. Further, these sites allow football fans to connect with others and provide their users with multiple features. The results also indicate that the use of Facebook and Twitter leads to football fanaticism due to negative communication, abuse of freedom, and lack of control. Furthermore, the respondents of this study pointed out two individual factors influencing football fanaticism through Facebook and Twitter, namely the absence of sportsmanship and over-reliance on Facebook and Twitter as sources of information.